The Development of Performance Assessment Instrument Integrated 4C for Measuring Science Process Skills in the Science Experiments of Elementary School Students - Wulandari, Betti Cahya; Rusilowati, Ani; Saptono, Sigit (Universitas Negeri Semarang, 2019)
The purpose of this research was to develop the assessment instrument of performance integrated 4C to measure the science process skills in the experimental activities at elementary schools. This research applied the Research and Development method. The development design was adjusted with the ADDIE model. The subjects of the research were grade V teachers and students in the second semester of 2018/2019 academic year at SDN Karangmlati 1 Demak. Based on the results of this research, it was obtained that the assessment instrument of performance integrated 4C has a validity of 93.12%, meanwhile, the validity of the process skills test instrument reached to 91.87%. The reliability of the assessment instrument of performance reached to 0.95, whereas, the reliability of the science process skills test instrument reached to 0.88. The practicality of the instrument reached to 86.4%. The highest percentage of science process skills of the students grade V in the aspect of planning the experiment skills reached a percentage of 93% (very high). This research is expected to help teachers carry out assessments of performance objectively and fairly that have a positive impact on the quality of learning at schools.